PENGARUH KETUAAN DAUN DAN METODE PENGOLAHAN TERHADAP AKTIVITAS ANTIOKSIDAN DAN KARAKTERISTIK SENSORIS TEH HERBAL BUBUK DAUN ALPUKAT (Persea americana Mill.) - Felicia, Naomi; Rai Widarta, I Wayan; Ariyusasrini, Ni Luh (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2017)
The objective of this study is to observe the influence of leaves maturity and processing methods to produce herb tea powder from avocado leaves with the best antioxidant activity and sensory characteristics. The treatments consisted of leaves maturity including young and old leaves, and processing methods including A method (steaming and drying) and B method (withering and pan firing). This study was designed using randomized block factorial and all data were analyzed statistically using ANOVA. The result of this study showed that old avocado leaves with A method had the best antioxidant activity and characteristics with moisture content 8,08%, total phenolic 21,48 mg GAE/g dry weight, total flavonoid 61,83 mg QE/g dry weight, antioxidant activity 84,89%, and sensory characteristics color was liked, flavor was slightly typical powdered tea and slightly liked, taste was slightly bitter and slightly liked, and overall acceptance was liked.
Keywords: antioxidant, avocado leaf, herb tea, tea powder